Nutraceuticals and cholesterol-lowering action. (March 2015) - Cicero, Arrigo F.G.; Parini, Angelo; Rosticci, Martina
Abstract: Nutraceuticals play an important role in cardiovascular prevention in patients with dyslipidemia. Many scientific studies support the use of these substances alone or associated with other drugs in clinical practice. Specifically, monacolines, berberine, policosanol and gamma-oryzanol could significantly reduce cholesterolemia. However, there is still an insufficient number of studies demonstrating morbidity and mortality outcomes of nutraceuticals, nor are sufficient data regarding the use of nutraceuticals in different types of patients, on tolerability, safety, target population, modality and duration of use present in the literature.